A simulation study on strategy to mitigate leadtime uncertainty risk in the context of information sharing - Padmapriya, P.; Kaur, Arshinder (Inderscience Publishers, 2012)
Lead time is an inseparable factor of any supply chain. Lead time uncertainty is known as one of the types of supply side risks or uncertainty that affects ordering policies, inventory levels and cost, and product availability level. Information sharing between supply chain members provides opportunities to reduce the inventory levels held to face such uncertainty thereby improving the performance of the supply chain. In this context, we study the effect of sharing the information regarding replenishment leadtime on total inventory costs in a two-level supply chain. In this paper, we have proposed two-level supply chain model to analyse the effects of leadtime information and to quantify the value of the information about lead-times to the retailer. We assume that the replenishment leadtime of the supplier is random and following uniform distribution and we consider two replenishment policies the first one for the case without information sharing and the second one with information sharing. With information sharing in place the retailer exercise the strategy of employing an emergency supplier to mitigate the leadtime uncertainty. The system under consideration is formulated as a mixed integer linear programming (MILP) problem and the simulation exercise results indicate that the value of leadtime information can be significant.